LA LLENGUA AL NOU ESTATUT D'AUTONOMIA DE CATALUNYA - Anna M. Pla Boix (Revista d'Estudis Autonòmics i Federals, 2006)
The purpose of the article is to analyse the linguistic regime established inCatalonia by the new Catalan Statute of Autonomy (new Catalan Statute).After preliminary reflection on the role of the regulation of this regime underthe new Catalan Statute, the article discusses the debates on the subjectthat arose during the drafting process of the later, before examining fourspecific regulations in it. First, it refers to the obligation to have a knowledgeof Catalan and the nature of such an obligation; second, to the consolidationof the legal position regarding the Aranés language ; and—followingthis—the article analyses the types of participation undertaken by the Spanishcentral government and the Generalitat (the Catalan Government) inthe foreign projection of the Catalan language at European and internationallevels, and in the relationship held with territories having linguisticassociations with Catalonia. Fourth and finally, it assesses recognition of acatalogue of linguistic rights in different public and private sectors (PublicAdministration and particularly the area of justice, and business) companies).In this sense, therefore, the article carries out a complete analysis ofthe new Statute’s contributions to the linguistic regime.